STUDENTS' DEMOGRAPHIC CHARACTERISTICS AND THEIR PERFORMANCE IN ECONOMICS IN OSUN STATE - Folasade Omotosho; Adesina B. A (PT. ZILLZELL MEDIA PRIMA, 2026)
The study examined the influence of secondary school students’ gender and socio-economic background on their academic performance. The study also determined the influence of secondary school students’ socio-economic background on their attitude toward Economics in Osun State, Nigeria. The research adopted a descriptive survey design. The population comprised all Senior Secondary School II students offering Economics in public schools across the state. A sample of 720 students was selected using a simple random sampling technique from twelve (12) schools. Data were collected using the Socio-Economic Background Questionnaire (SEBQ), Mathematical Economic test (MET) and Economics Students’ Attitudinaire (ESA), and they were analysed using mean, standard deviation, and Pearson Product-Moment Correlation. The findings revealed that gender significantly influenced students’ academic performance in Economics (R = -0.14; p < 0.05), with female students outperforming males. Similarly, socio-economic background had a significant positive influence on students’ attitude towards Economics (R = 0.29; p < 0.05). Based on the findings, it was recommended that schools should adopt gender-responsive instructional strategies and provide support mechanisms for students from low-income backgrounds to improve both performance and disposition toward Economics.